Efektivitas Ekstrak Lipid Total Mikroalga (Nannocloropsis Oculata) Dalam Menghambat Pertumbuhan Bakteri Hasil Isolasi Pasca Pencabutan Gigi - Rasmi Putri Santoso; Eddy Hermanto; Syamsulina Revianti (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: Tooth extraction is a treatment procedure that was usually done by a dentist. It has known that the total lipid extraction of microalgae (Nannochloropsis oculata) has antifungal and Gram-positive and Gram-negative antibacterial. Total lipid extract of microalgae 1FAME (fatty acid methyl ester) of total lipid extract microalgae (Nannochloropsis oculata) has the ability to inhibit bacteria. Objective: To know the effectiveness of total lipid extract of microalgae (Nannochloropsis oculata) in inhibiting the growth of bacteria aerobic and anaerobic isolated after tooth extraction. Materials and methods: This research was true experimental research design with post test only control group design. Objects were divided into 10 groups (5 Aerobic and Anaerobic 5), using diffusion method. Negative control were hexane 1%, positive control were amoxicillin 25μg, treatment were total lipid extract of microalgae (Nannochloropsis oculata) with concentration 1.5%, 3% and 6%. Samples were taken using a power point size 45 inserted into the socket former tooth extraction. Samples were incubated and identified, then given 5 treatments (negative control, positive control, microalgae (Nannochloropsis oculata) 1.5%, 3% and 6%. Results: Mann-Whitney showed there are differences between the inhibitory control and treatment groups microalgae (Nannochloropsis oculata). Conclusion: Total lipid extract of microalgae (Nannochloropsis oculata) was able to inhibit bacterial aerobic and anaerobic isolated post-tooth extraction.